2014
DOI: 10.1103/physrevb.89.045140
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous nonadditive dispersion interactions in systems of three one-dimensional wires

Abstract: The non-additive dispersion contribution to the binding energy of three one-dimensional (1D) wires is investigated using wires modelled by (i) chains of hydrogen atoms and (ii) homogeneous electron gases. We demonstrate that the non-additive dispersion contribution to the binding energy is significantly enhanced compared with that expected from Axilrod-Teller-Muto-type triple-dipole summations and follows a different power-law decay with separation. The triwire non-additive dispersion for 1D electron gases sca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…22 The inherent delocalization of free electrons in metals coupled with low dimensionality leads to an especially slow decay of the vdW force between metallic chains and layers as a function of their separation, 23 a modification of the conventional asymptotic behavior which dominates at very large distances (e.g., beyond 10−20 nm in bilayer graphene). 104 In this context, Misquitta et al 105,106 demonstrated that, upon closure of the band gap, semiconducting nanowires may also exhibit unconventional power-law behavior at intermediate separations, followed by asymptotic convergence to the pairwise-additive limit.…”
Section: Conceptual Understanding Of Vdw Interactions In Molecules Anmentioning
confidence: 99%
“…22 The inherent delocalization of free electrons in metals coupled with low dimensionality leads to an especially slow decay of the vdW force between metallic chains and layers as a function of their separation, 23 a modification of the conventional asymptotic behavior which dominates at very large distances (e.g., beyond 10−20 nm in bilayer graphene). 104 In this context, Misquitta et al 105,106 demonstrated that, upon closure of the band gap, semiconducting nanowires may also exhibit unconventional power-law behavior at intermediate separations, followed by asymptotic convergence to the pairwise-additive limit.…”
Section: Conceptual Understanding Of Vdw Interactions In Molecules Anmentioning
confidence: 99%
“…With an influence ranging from protein-drug binding to the double helix in DNA [5], the peculiar pedal adhesion in the gecko [6,7], and even cohesion in regolith and rubble-pile asteroids [8,9], these nonbonded forces are quantum mechanical in origin and arise from electrodynamic interactions between the constantly fluctuating electron clouds that characterize molecules and materials [10]. While our understanding of vdW interactions is rather complete at the smallest atomistic and the largest macroscopic scales, these pervasive forces exhibit a range of surprising and poorly understood effects at the nanoscale [10][11][12][13][14][15][16].This lack of understanding is best exemplified by recent puzzling experimental observations, which include (i) ultralong-range vdW interactions extending up to tens of nanometers into heterogeneous Si/SiO 2 dielectric interfaces [17,18], and influencing the delamination of extended graphene layers from silicon substrate [19]; (ii) complete screening of the vdW interaction between an atomic force microscope (AFM) tip and a SiO 2 surface by the presence of a single layer of graphene adsorbed on the surface [20]; (iii) superlinear sticking power laws for the physical adsorption of metallic clusters on carbon nanotubes with increasing surface area [21]; and (iv) nonlinear increases in the vdW attraction between homologous molecules and an Au(111) surface as a function of the molecular size [22]. Recently, theoretical evidence was found for exceptionally long-ranged vdW attraction between coupled low-dimensional nanomaterials with metallic character [11] or small band gap [10,14].…”
mentioning
confidence: 99%
“…With an influence ranging from protein-drug binding to the double helix in DNA [5], the peculiar pedal adhesion in the gecko [6,7], and even cohesion in regolith and rubble-pile asteroids [8,9], these nonbonded forces are quantum mechanical in origin and arise from electrodynamic interactions between the constantly fluctuating electron clouds that characterize molecules and materials [10]. While our understanding of vdW interactions is rather complete at the smallest atomistic and the largest macroscopic scales, these pervasive forces exhibit a range of surprising and poorly understood effects at the nanoscale [10][11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…Arising from nonlocal electrodynamic correlations between instantaneous charge fluctuations in matter, vdW interactions are quantum mechanical in nature with an influence that spans distances (D) ranging from atomic dimensions (i.e., a fewÅ) to well beyond the nanoscale [33][34][35]. At these distances, dimensionality, local response properties, and While analytic vdW scaling laws (such as D −5 or D −4 for two parallel insulating wires or plates) are central to our understanding of infinite-size systems at asymptotic distances, rather unusual power laws have been observed in both finite and extended systems at intermediate distances relevant to the nanoscale [37][38][39][40][41][42][43][44][45]. For example, Gould et al [38] argued that the binding energy of graphite varies as D −4 for non-asymptotic interlayer separations, which differs from the asymptotic D −3 behavior analytically demonstrated by Dobson and coworkers [38,46,47]; this was later confirmed by high-level quantum mechanical calculations [39,41], which found D −4.2 for D ≈ 3−9Å.…”
mentioning
confidence: 99%
“…Since the inclusion of many-body vdW interactions often leads to power laws with significant deviations from conventional pairwise predictions [37,43,[51][52][53][54][55], we now consider how an infinite-order many-body expansion of E A−ann vdW would influence the vdW scaling behavior in the presence of a pore. Under the same assumptions, we computed P A−ann vdW for the smallest (r = 1Å) and largest (r = R = 10Å) pore sizes considered above within the random phase approximation (RPA) of the ACFDT (see Supplemental Material) [56].…”
mentioning
confidence: 99%